رأس المال النفسي وعلاقته ببعض المتغيرات لدى منتسبي الجامعة من التدريسيين والموظفين - مطشر الكعبي سهام; سعيد المشايخي اركان (Al-Adab Journal, 2018)
Psychological capital and its relationship to some variables for The University staff member’s teachers and employees. The current research aims mainly to measuring psychological capital in the university environment, as well as other objectives related to the nature of the difference in psychological capital according to a number of demographic variables such as job (University teachers, employee), gender (male, female) (Scientific, human) with regard to the category of teachers. The current research was determined by a sample of (230) members of Baghdad University selected according to the variables above.In order to achive objectives of the research the researchers constructed a scale of the psychological capital and then verified its psychometric properties and settled on (23) items with a 5 points. After analyzing the data using the T-test of one sample and two independent samples and Tow way anova, the research reached the following results: There is a high level of psychological capital in the entire research sample. There is a high level of psychological capital in the sample of teachers in general and regardless of the variables of gender and specialization. There is no significant difference in the psychological capital among the scientific and human subjects of the teachers in the research sample. There is a high level of psychological capital in the sample of employees in general and regardless of gender variable. There is a high level of psychological capital in the male sample in general and regardless of the variables of the job and specialization for the teachers. There is a high level of psychological capital in the female sample in general and regardless of the variables of the job and specialization for the teachers. There has been a statistically significant difference in the psychological capital according to the variable of the job (teachers, employees) and for the benefit of the teachers. 8 .There was a statistically significant difference between males and females in psychological capital in the whole sample and in favor of males. There was no statistically significant effect on psychological capital depending on the interaction of both gender and function variable. Acording to the results obtained a number of recommendations and proposals were presented.